Semiosis as individuation: Integration of multiple orders of magnitude - Karatay, Vefa; Denizhan, Yağmur; Ozansoy, Mehmet (Springer Netherlands, 2016)
This paper proposes Gilbert Simondon’s ontogenetic theory of individuation as an overarching framework for multilevel semiosis. What renders this theory suitable for this role is the fact that it shares a significant part of its heritage with biosemiotics, which provides compatibility between them. Unlike many philosophers who have worked on individuation, Simondon envisages a general process of individuation that starts with a metastable preindividual. This process ultimately constitutes an axiomatisation of ontogenesis and manifests itself in three basic modes: physical, vital and psycho-collective. In any of these modes a transductive operation is at work resolving the disparities of the preindividual whereby new structures emerge. Depending on the mode of individuation, the emerging structures can create new disparities that ask for further individuation. Simondon refers to such conversion of structure to operation and vice versa as allagmatics. He also extends his theory to scientific methodology establishing a healthy balance between reductionism and holism. His theory can be used to amend Peircean metaphysics to improve its compatibility with contemporary scientific discourse.
Keywords: Allagmatics; Individuation; Ontogenesis; Semiosis; Transduction